Reactive oxygen species regulate miR‐17‐5p expression via DNA methylation in paraquat‐induced nerve cell damage. Issue 12 (21st July 2020) - Zhan, Yanting; Guo, Zhenkun; Zheng, Fuli; Zhang, Zhipeng; Li, Ke; Wang, Qingqing; Wang, Lijin; Cai, Zhipeng; Chen, Nengzhou; Wu, Siying; Li, Huangyuan
Abstract: There is emerging evidence suggesting that oxidative stress and DNA methylation can alter miRNA expression. However, little is known on the mechanism of miR‐17‐5p expression changes in paraquat (PQ)‐induced nerve cell damage. In the present study, neuro‐2a cells were pretreated with antioxidant N‐acetylcysteine (NAC) or DNA methylation inhibitor decitabine (DAC), then exposed to different concentrations of PQ, while the expression levels of miR‐17‐5p were detected by qRT‐PCR. Here, it is showed that PQ downregulated the expression of miR‐17‐5p dose‐dependently in neuro‐2a cells. The DNA methylation level was upregulated after PQ exposure, while downregulated with the pretreatment of NAC in the above content, detected by 5‐mC immunofluorescence technique. The interaction effect of NAC and PQ in alternating DNA methylation level was further confirmed by flow cytometry. NAC and DAC individually had an interaction effect in PQ‐induced nerve cell damage. After using NAC, PQ‐induced ROS elevation and DNA methylation are reduced, thereby preventing the proapoptotic effect of miR‐17‐5p. Above all, PQ can induce DNA methylation variations through ROS production, leading to the downregulation of miR‐17‐5p expression in PQ‐induced nerve cell damage.